The ABC Analysis of Drug Use and Cost in Cardiology Outpatients -National Health Insurance - Budi Suprapti; M. Yusuf; Marcha Debby Saraswati; Selvia Febriana Astuti; Dewi Damayanti (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Cardiovascular disease is one of the chronic diseases with an increasing prevalence from year to year. The results of Indonesia's basic health research (RISKESDAS 2018) showed that it was experienced by 2.9% of the population. Ensuring the continuity of drug availability is very important in pharmacy services for this patient group. The history of drug use is considered in the planning dan procurement of drug products. Objective: This study aims to analyze the drug use pattern and cost of drugs for cardiology outpatients in the National Health Insurance scheme (JKN). Methods: A retrospective observational study was conducted using the prescription of cardiology outpatients JKN for March-May 2021. The ABC method carried out the analysis of drug use patterns and cost. Results: From 2,986 prescriptions for cardiovascular disease, there were 94 types of drugs from 37 therapeutic classes. In the ABC analysis of drug use for class A, 68.82% contained seven types of drugs, class B, 20.55% contained nine types of drugs, and class C, 10.63% with 78 types of drugs. The results of ABC analysis for investment value (cost) of drugs class A 66.96% contained two types of drugs, class B 19.81% with four types of drugs, and class C 14.23% with 88 types of drugs. Conclusion: ABC analysis of the drug use pattern and cost/investment showed different patterns which had value to consider in procurement planning to maintain service continuity.